Charge and spin transport in disordered graphene-based materials : doctoral thesis accepted by Autonomous University of Barcelona, Spain /: doctoral thesis accepted by Autonomous University of Barcelona, Spain. ([2016]) - Van Tuan, Dinh
No abstract available